(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article provides a comprehensive philosophical analysis of the spiritual life and moral foundations of the existence of the Kyrgyz people, which were embodied in the creative heritage. This is the development of various kinds of national crafts and crafts, as a result of the geographical location of the Kyrgyz, their habitats on the “Great Silk Road”. The presented results of the analysis will be able to replenish to a certain extent the theoretical and methodological base of research on a number of aspects of social philosophy in the context of the social life of the Kyrgyz people